Measuring the immune system of the three-spined stickleback: investigating natural variation by quantifying immune expression in the laboratory and the wild - Robertson, Shaun; Bradley, Janette E.; MacColl, Andrew D.C. (Wiley, 2016)
Current understanding of the immune system comes primarily from lab-based studies. There has been substantial interest in examining how it functions in the wild, but studies have been limited by a lack of appropriate assays and study species. The three-spined stickleback (Gasterosteus aculeatus L.) provides an ideal system in which to advance the study of wild immunology, but requires the development of suitable immune assays. We demonstrate that meaningful variation in the immune response of stickleback can be measured using real-time PCR to quantify the expression of eight genes, representing the innate response and Th1, Th2 and Treg type adaptive responses. Assays are validated by comparing the immune expression profiles of wild and laboratory raised stickleback, and by examining variation across populations on North Uist, Scotland. We also compare the immune response potential of laboratory raised individuals from two Icelandic populations by stimulating cells in culture. Immune profiles of wild fish differed from laboratory-raised fish from the same parental population, with immune expression patterns in the wild converging relative to those in the laboratory. Innate measures differed between wild populations, whilst the adaptive response was associated with variation in age, relative size of fish, reproductive status and S. solidus infection levels. Laboratory-raised individuals from different populations showed markedly different innate immune response potential. The ability to combine studies in the laboratory and in the wild underline the potential of this toolkit to advance our understanding of the ecological and evolutionary relevance of immune system variation in a natural setting.